Timber Mountain Caldera Landscape Photograph Collection - Stoffle, Richard W. (Bureau of Applied Research in Anthropology, University of Arizona, 2013)
These photographs offer illustrations of the people, places, and resources along the two prominent pilgrimage trails in the Timber Mountain Caldera region. These photographs were taken during the 2006 Timber Mountain Caldera Landscape Study, the 2001 Shoshone Mountain Wind Farm Environmental Assessment, and 1999 NTS Rock Art study.